2010
DOI: 10.1245/s10434-010-0947-x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Risk Score to Predict In-Hospital Mortality After Pancreatic Resection for Cancer

Abstract: An integer-based risk score can be used to accurately predict in-hospital mortality after pancreatectomy and may be useful for preoperative risk stratification and patient counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 11 publications
3
71
1
Order By: Relevance
“…This method of risk score development has been described previously. 18,[20][21][22] Separate risk scores were developed for both 30-day morbidity and mortality after DP.…”
Section: Development Of a Risk Score Modelmentioning
confidence: 99%
“…This method of risk score development has been described previously. 18,[20][21][22] Separate risk scores were developed for both 30-day morbidity and mortality after DP.…”
Section: Development Of a Risk Score Modelmentioning
confidence: 99%
“…21,22 Another, the SOAR score, considers a patient's preoperative condition using the Charlson comorbidity scale as a foundation. 23 Still others, derived from the ACS-NSQIP database, blend elements of both. 24,25 While these may be effective at segregating outcomes at the population level, the real ability of these tools to forecast an actual, individual mortality is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Other studies have reported differences in cancer survival by surgeon and hospital case load, with higher case loads generally being associated with higher survival. 16,[19][20][21][22][23][24][25][26][27] Often these were studies of other cancers, although higher survivals from breast cancer have been linked to higher case loads in North America, Europe, Asia and Western Australia. [28][29][30][31][32][33][34][35][36][37][38][39][40] Results have generally been interpreted as reflecting higher skill development from managing higher case loads, although this interpretation has been questioned and alternative explanations suggested, including accompanying differences in degree of specialisation, access to multidisciplinary conferencing, and availability of specialist adjunctive services.…”
Section: Introductionmentioning
confidence: 99%